2022
DOI: 10.3389/fpsyg.2021.773030
|View full text |Cite
|
Sign up to set email alerts
|

Couples Therapy Delivered Through Videoconferencing: Effects on Relationship Outcomes, Mental Health and the Therapeutic Alliance

Abstract: Changing technology, and the pervasive demand created by a greater need in the population for access to mental health interventions, has led to the development of technologies that are shifting the traditional way in which therapy is provided. This study investigated the efficacy of a behavioral couples therapy program conducted via videoconferencing, as compared to face-to-face. There were 60 participants, in couples, ranging in age from 21 to 69 years old. Couples had been in a relationship for between 1 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…Given the influence of specific media affordances on the type of relation that can be built and on the relational practices that can and must be employed by the participants (Muntigl et al 2013;Stommel and Te Molder 2015;Linke and Schröter 2017), another empirical focus addresses the medium in and through which the helping relationship materializes (cf. Ekberg et al 2016;Berger 2017;Van Daele et al 2020;Kysely et al 2022). While most contributions draw on face-to-face interaction in the context of verbal communication, embodied practices of relationship building and their combination with verbal practices are at the center of the contribution by Muntigl.…”
Section: The Current Volume: Aims and Scope Research Questions And Me...mentioning
confidence: 99%
“…Given the influence of specific media affordances on the type of relation that can be built and on the relational practices that can and must be employed by the participants (Muntigl et al 2013;Stommel and Te Molder 2015;Linke and Schröter 2017), another empirical focus addresses the medium in and through which the helping relationship materializes (cf. Ekberg et al 2016;Berger 2017;Van Daele et al 2020;Kysely et al 2022). While most contributions draw on face-to-face interaction in the context of verbal communication, embodied practices of relationship building and their combination with verbal practices are at the center of the contribution by Muntigl.…”
Section: The Current Volume: Aims and Scope Research Questions And Me...mentioning
confidence: 99%
“…The only clinical trial to date to date to systematically examine a couple therapy delivered over TMH compared to an in-person modality demonstrated comparable clinical benefit from a couple-based posttraumatic stress disorder (PTSD) treatment when delivered in-person or over TMH-V (Morland et al, 2022). Another recent randomized study showed equivalent treatment gains and working alliance when providing relationship education over TMH compared to face-to-face (F2F; Kysely et al, 2022). More research is needed on how TMH is used to provide VA couple and family services and which patients may be best served by this modality.…”
mentioning
confidence: 99%